Pengaruh Metode Mind Mapping terhadap Kreativitas Belajar Siswa Pada Mata Pelajaran IPS Kelas VIII MTs NW Pringgasela: Influence of Mind Mapping Method on Student Creativity in Class VIII Social Science Subjects MTs NW Pringgasela - Ittihad (Pendidikan Al-Gafari, 2025)
Learning cannot be separated from others and also cannot be delegated to others. Learning is only possible if the child wants it, according to his/her wishes, and experiences it himself/herself, meaning that students learn because of their interests and motivations so that with their own awareness, students will try to achieve maximum results. This research is a kind of experimental study aimed to determine the effect of learning mtode use Mind Mapping to creativity eighth grade social studies students MTs NW Pringgasela. The subjects were students of class VIII MTs NW Pringgasela totaling 53 people. The samples in this study were students of class VIII MTs NW Pringgasela, experimental class 26 and class 27 controls. Data collection techniques using test and observation techniques. The data analysis using normality test, test and test hypotheses homogentitas using t-test formula. The results obtained for the average value of the experimental class = 77.00. As for the control class average value = 71.30 there is a difference or the difference between the average value of the experimental class and control class is = 5.7 and the results of hypothesis testing using the formula t test = 2.960 from the results of this study concluded that the application of the method Mind Mapping learning krativitas effect on student learning in social studies classes VIII MTs NW Pringgasela.